Implementation of Affirmative Action for Persons with Disabilities in Recruitment of Election Organizers - Chabibullah, Moch (IHSA Institute, 2024)
Discriminatory treatment of people with disabilities is an example of a human rights violation. They have the same right to get the accessibility support needed to support the participation of people with disabilities in various aspects of life. To change existing problems, the first step is to change the perspective towards people with disabilities. Affirmative action is the most appropriate weapon to fight acts of discrimination. Disrespectful treatment needs to be provided with concrete evidence by people with disabilities. Providing a real portion like women is an action that is currently needed by people with disabilities in order to balance an advanced society and pay attention to the mandate of the law that equality in the law is something that must be recognized and urgently realized. Fulfillment of the political rights of persons with disabilities is very clearly written in Law Number 8 of 2016 concerning Persons with Disabilities, this law becomes a more special norm (Lex Specialist), even defeating Law Number 7 of 2017 concerning General Elections (Lex Generalis ). The legal rules state that